(untitled) (Research, Society and Development, 2022)
Introduction: The pandemic triggered by SARS-CoV-2 brought challenges to the care of patients with AMI, affecting adequate care. In this study, the objective was to carry out an integrative review to analyze the impact of the COVID-19 pandemic on the delay of care for patients with AMI and, consequently, on their prognosis. Methodology: This is an integrative, qualitative literature review with a descriptive approach. A survey of articles was carried out in the main databases using the descriptors “COVID-19”, “Myocardial Infarction” and “STEMI”; and the Boolean operator AND. The inclusion criteria were: original article, available in full for free access, published in 2020 and 2021, in Portuguese, English and/or Spanish. The final sample consisted of 32 articles. Results: Retrospective cohort, retrospective observational study and meta-analyses were used in the article. These studies reported an almost 80% reduction in the admission of patients with AMI. The prognosis was worse during the pandemic period with an increase in the number of complications and an increase in morbidity and mortality. Mortality from AMI increased by 1.3% to 80% in the period of the pandemic when compared to the same period in the previous year pre-pandemic. In addition, some studies found that the mortality of patients with AMI and COVID-19 could increase by up to four times when compared to the patient with COVID alone. Conclusion: There is a reduction in admissions of AMI cases that may be linked to the fear of contamination and social isolation measures that, associated with the overload of the health system, have led to a delay in seeking care.